The expression of lnc-CCDC170-4:1, ESR1, lncRNA SRA, and CYP19A1 in cervical squamous cell carcinoma and their relationship with the clinical characteristics - Yuan, Jinrui; Wen, Mengke; Matnuri, Amina; Zhao, Shihong; Jian, Ning; Shen, Guqun (Frontiers in Oncology, 2024)
Introduction: The occurrence of cervical cancer may be related to estrogen and estrogen receptors. This study investigated the expression of lnc-CCDC170-4:1, ESR1 (estrogen receptor 1), lncRNA SRA, and CYP19A1 (aromatase) in cervical squamous cell carcinoma tissues, as well as their relationship with the clinical characteristics of patients. Methods: Whole transcriptome sequencing analysis was performed on cervical squamous cell carcinoma tissues (n=4) and normal tissues (n=4). The expressions of lnc-CCDC170-4:1, ESR1, lncRNA SRA, and CYP19A1 were validated in 26 cases of cervical cancer tissue and 30 cases of normal cervical tissue using qRT-PCR. The relationship of gene expression with the clinical characteristics and 5-year overall survival rates of cervical cancer patients was analyzed. Results: The expression levels of CYP19A1 and lncRNA SRA were upregulated, while those of ESR1 and lnc-CCDC170-4:1 were downregulated in cervical squamous cell carcinoma tissue. However, their expression was not related to 5-year overall survival rates (p>0.05). Low expression of lnc-CCDC170-4:1 was associated with lymph node metastasis (p=0.030)and Tumor size(p=0.047) ，Low expression of ESR was associated with FIGO Staging(p=0.041)and Tumor size(p=0.002),High expression of LncSRA was associated with FIGO Staging(p=0.004). Conclusions: Estrogen and estrogen receptors may play a role in the occurrence and development of cervical squamous cell carcinoma. Low expression of lnc-CCDC170-4:1 and ESR1 are associated with lymph node metastasis and FIGO stage, so it may be a potential biomarker to evaluate the prognosis of cervical cancer.